Influence of Trust on Knowledge Sharing mediated by Transformational Leadership - Ade Irma Angreani, Woori Vivi Wulandari, Adriana Madya Maramp,Pramono Hari Adi (International Journal of Advanced Science and Technology, 2020)
The significance of trust is highly pertinent when it comes to knowledge sharing in an organization. Knowledge management is initiated by knowledge sharing as one of its most basic processes. A leader is needed to create and carry out knowledge sharing of an organization, especially in MSMEs. Transformational is very important in influencing a knowledge sharing in MSME organizations. The study was conducted on Knowledge Sharing MSME employees in organizations, especially Micro, Small and Medium Enterprises. different from a big business. Knowledge sharing at UMKM is usually done informally while the Corporate Business is done formally. Research is conducted at UMKM employees. The sample used in this research is 160. This research uses SEM-PLS. The results indicated that Trust significantly affects Knowledge Sharing. Transformational leadership significantly affects knowledge sharing through its role as a moderator.